2011
DOI: 10.1038/aja.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and social aspects of infertility in men: an overview of the evidence and implications for psychologically informed clinical care and future research

Abstract: Research concerning the psychosocial aspects of infertility and infertility treatment focuses more often on women than men. The aim of this review was to synthesize the English-language evidence related to the psychological and social aspects of infertility in men and discuss the implications of these reports for clinical care and future research. A structured search identified 73 studies that reported data concerning the desire for fatherhood and the psychological and social aspects of diagnosis, assisted rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
172
1
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(193 citation statements)
references
References 81 publications
7
172
1
13
Order By: Relevance
“…The experience of infertility or involuntary childlessness (the preferred term used in this paper) is also influenced by the social context in which it takes place, including socioeconomic status, religion, culture, gender, gendered practices and direct and indirect messages women and men receive (Bell, 2016). While women using assisted conception experience greater levels of distress than men (Greil, Slauson-Blevis, & McQullian, 2010), men too may need to cope with anxiety or depression (Fisher and Hammarberg, 2012). They may invest time and emotional efforts into diagnostic investigations and providing sperm samples, as well as supporting their partner through the numerous tests and invasive treatment processes.…”
Section: Introductionmentioning
confidence: 99%
“…The experience of infertility or involuntary childlessness (the preferred term used in this paper) is also influenced by the social context in which it takes place, including socioeconomic status, religion, culture, gender, gendered practices and direct and indirect messages women and men receive (Bell, 2016). While women using assisted conception experience greater levels of distress than men (Greil, Slauson-Blevis, & McQullian, 2010), men too may need to cope with anxiety or depression (Fisher and Hammarberg, 2012). They may invest time and emotional efforts into diagnostic investigations and providing sperm samples, as well as supporting their partner through the numerous tests and invasive treatment processes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in normal couples reveal that 90% of them will conceive within one year of unprotected intercourse. Thus, the classic definition of infertility became the absence of conception after one year of regular and unprotected intercourse (1). However, because a small number of normal couples will conceive between 12 and 24 months, the world health organization (WHO) has suggested that absence of conception after 24 months of unprotected intercourse is the preferred definition of infertility (2).…”
Section: Introductionmentioning
confidence: 99%
“…The negative consequences found in many studies and reviews included increased levels of stress, confusion and anxiety [5] [6] [7], decreased satisfaction with the couples' relationship and sexuality [8] [9], decreased satisfaction with social life and, in unsuccessful treatments, hampered grieving [10] [11] and lasting sadness [12]. These negative consequences are found in both men and women, and while some authors suggest these consequences may be somewhat stronger in women [8] [13] [14], others did not [12] [15]. A successful fertility treatment does not resolve all negativity, as parents who conceived through fertility treatment had higher levels of anxiety in early pregnancy [5] [16] and perceived pregnancy as being more risky and demanding [17] [18].…”
Section: Introductionmentioning
confidence: 99%